BIBLIOGRAFI BERANOTASI TENTANG SITUS KERATON RATU BOKO - Nurhadi Rangkuti (Berkala Arkeologi, 2003)
The site of the Ratu Boko Palace, which is located on a hillside in the Prambanan area, Yogyakarta, is an archaeological relic of the Old Mataram Kingdom (8-10 century AD). The temple complex consists of three groups of buildings, namely (1) the western part, which is a three-story courtyard. The three pages are connected by closed gates (paduraksa). On these courtyards there are remains of buildings that have now been restored, (2) Southeastern part, in the form of a group of buildings consisting of two parts. One part is a stone floor with a stone fence. This building is called the "pendopo". The other part is in the form of pools with buildings called "keputren", and around it there are small buildings in the form of temples which are located above the pools, (3) the northeast part, which are three caves located on the hillside. Apart from these three groups, there are still many other remains whose form and function are not clear.